A Counterfactual Analysis of the Poverty Impact of Economic Growth in Cameroon - Essama-Nssah, B.; Bassole, Leandre (2012)
The Government of Cameroon has declared poverty reduction through strong and sustainable economic growth the central objective of its socioeconomic policy. This paper uses available household survey data to assess the performance of the economy with respect to this objective over the period 1996-2007. The authors use counterfactual decompositions based on both the Shapley method and the generalized Oaxaca-Blinder framework to identify proximate factors that might explain differences in observed outcomes over time, across regions and households. The concept of pro-poorness provides a basis for a normative evaluation of these outcomes. The analysis of changes in the size distribution of economic welfare reveals that formal sector employment, access to credit, education, and urban residence are characteristics that bring significantly high returns to households. Employment in smallholder agriculture has a negative impact on welfare across quantiles. Economic growth was accompanied by significant poverty reduction between 1996 and 2001. But poverty barely decreased between 2001 and 2007 due to very weak growth. Over the same period, household investment in human capital took a serious hit. Given the additional finding that the pattern of growth is characterized by urban bias and regional disparity, the overall assessment is that economic growth has been weakly pro-poor in Cameroon. There is therefore a need to re-examine and possibly reform the mechanisms governing the allocation of public resources designed to support individuals' efforts to improve their standard of living.